Apple's Critique - Mmalefikane Sylvia SEPENG (Annals of the University of Craiova for Journalism, Communication and Management, 2025)
This article explores Michael Apple's perspectives on the official curriculum and their implications for teacher attrition. Drawing on Apple's critical theory of education, it examines how ideological and economic forces shape curriculum content and pedagogical practices in ways that can contribute to teacher burnout and attrition. The analysis focuses on four key themes